NOD2 (Nucleotide-Binding Oligomerization Domain-Containing Protein 2)-Mediated Modulation of the Immune Response Induced by BCG (Bacillus Calmette-Guérin) Bacilli - Magdalena Jurczak; Joanna Kaczmarek; Magdalena Kowalewska-Pietrzak; Paulina Stelmach; Magdalena Druszczynska (Pathogens, 2025)
The Bacillus Calmette-Guérin (BCG) vaccine confers broad, non-specific immunity that may bolster defenses against respiratory viruses. While NOD2 (nucleotide-binding oligomerization domain-containing protein 2)-driven pathways are central to innate immune responses, the contribution of surface receptor modulation on monocytes to shaping these responses remains underexplored. We analyzed whole-blood cultures from BCG-vaccinated Polish children, stratified by serostatus to SARS-CoV-2 and RSV, and stimulated for 48 h with live BCG, purified viral antigens, or both. RT-qPCR quantified mRNA levels of NOD2 and key cytokines (IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, TNF), while flow cytometry assessed CD14, HLA-DR, CD11b, and CD206 expression. Co-stimulation with BCG + RSV elicited the strongest transcriptional response, notably a 2–4-fold upregulation of NOD2, IL-1β, and IL-6 versus RSV alone. In SARS-CoV-2(+) donors, RSV alone induced higher NOD2 expression than BCG or BCG + RSV, while IL-2 peaked following BCG + SARS-CoV-2. Across conditions, NOD2 positively correlated with IL-4 and IL-6 but negatively correlated with IL-1β in SARS-CoV-2 cultures. Viral antigens increased CD14 and HLA-DR on monocytes, suggesting activation; CD206 rose only in dual-seropositive children. Our findings indicate that BCG stimulation affects pediatric antiviral immunity through NOD2-related cytokine production and induction of a CD14+HLA-DR+ phenotype, supporting its potential role in boosting innate defenses against respiratory pathogens.